Factors associated with recurrence of postoperative meningioma - Alfotih Gobran (Romanian Neurosurgery, 2013)
Background and purpose: As the postoperative recurrence of meningioma can have devastating effects, it is important to identify factors that can be used to predict this type of tumor recurrence. Material and methods: We have performed a retrospective study involving 138 patients who were surgically treated for intracranial meningioma between 2005 and 2010. The patient population consisted of 80 females and 58 males, with an age range of 23 to 77 years old (mean age = 52 years). We measured associations between meningioma recurrence and clinical features (age, sex, extent of resection, histological type), or radiological features (tumor size, location, shape, calcification, bone changes, brain tumor interface, tumor necrosis, and MRI enhancement). Results: We found statistically higher levels of postoperative meningioma recurrence in patients with high Simpson grade resections, high histological types, tumor diameters > 5 cm, tumors located in the base of the skull or the parasagittal sinus, tumors with unclear border, irregular enhancements on MRI, edema around the tumor, bleeding and necrosis within the tumor, and irregularly shaped tumors (e.g., lobulated or mushroom-shaped). In addition, calcification, age, sex, bone change, and dural tail sign provided no predictive value. Conclusions: We have shown that histological type, degree of resection, bleeding, necrosis, edema, irregular enhancement, location, shape, size, and margin serve as strong predictors for the postoperative recurrence of meningioma tumors.